Feed intake of does and their litters in different environmental temperatures - Fernández Carmona J.; Cervera C.; Blas E. (Rabbit production in hot climates, 1994)
Ninety-five crossbreed New Zealand does were maintained in a traditional rabbitry with daily minimum temperatures ranging from 11 to 28 degrees Celsius or at constant temperature of 30 degrees Celsius, and fed ad libitum on a diet with 11.2 MJ DE/kg DM. Food intake at 12, 18, 24 and 30 degrees Celsius mean minimum temperatures were examined from 279 lactations, using litter size as a covariate. Food intake of does and litters was always lower at 30 degrees Celsius. In the traditional rabbitry, ingestion of does was similar at all temperatures for the ten last days of gestation and the first week of lactation, but was lower at 24 degrees Celsius for the first three weeks of gestation and second, third, fourth and fifth weeks of lactation. Food intake of litters was lower at 12 degrees Celsius.
1. International Conference of rabbit production in hot climates, 1994/09/06-08, Cairo (Egypt)